SOCIAL NETWORK FOR LEARNING: AL-HIKMAH UNIVERSITY UNDERGRADUATE STUDENTS’ PERSPECTIVE - Semiu Olawale Makinde (Sanata Dharma University Yogyakarta, 2020)
This study was carried out to investigate the awareness and utilization of social network for learning among undergraduate students at Al-hikmah University, Ilorin, Nigeria. Gender, technology background, age, level, and area of specialization are the variables involved. The descriptive survey research design was employed to draw responses with the use of self-structured questionnaire. All Al-hikmah university students are the population of the study while the target population are 200 level to 400 level students from which a sample size of 400 undergraduate students was selected via random sampling techniques from six out of seven faculties available. The instrument was validated by experts and the reliability co-efficient using a split-half test was 0.86. Four research questions and one hypothesis were used for the study. Frequency distribution, charts, and t-test were the statistical tools used to analyze the data. The findings indicated that social network is used for educational purposes with improved engagement, better understanding of the subject matter as it helps to reinforce learning with technology because 80.0% of learners were digital native. Despite the benefits, social network can interrupt personal study, distract the conventional classroom learning, loss of privacy and exposure to cybercrimes as indicated by the respondents with 82%, 68%, and 55% respectively. Hence, Tertiary Institutions should organize series of seminars, workshops, conferences to update, enlighten and encourage students and lecturers on the good and not forgetting the not too- good and disadvantages attached with the use of social network as a tool for learning and interaction.